2016
DOI: 10.1017/s0022215116008537
|View full text |Cite
|
Sign up to set email alerts
|

Nasal airflow and brain activity: is there a link?

Abstract: This article explores these theories in detail, reviews the evidence, and presents new models linking nasal airflow and brain activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 56 publications
(137 reference statements)
0
24
0
Order By: Relevance
“…However, findings have not been consistent in this regard and the mechanism is not clear yet. The cyclical alteration in airflow dominance between the right and left nostrils (also called as nasal cycle ) associated with lateralized rhythms in autonomic activity is proposed as a possible mechanism in this regard (Price & Eccles, 2016; Shannahoff‐Khalsa, 1991), though definitive evidence confirming this is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, findings have not been consistent in this regard and the mechanism is not clear yet. The cyclical alteration in airflow dominance between the right and left nostrils (also called as nasal cycle ) associated with lateralized rhythms in autonomic activity is proposed as a possible mechanism in this regard (Price & Eccles, 2016; Shannahoff‐Khalsa, 1991), though definitive evidence confirming this is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the latest of a recent series of articles on nasal airflow in The Journal of Laryngology & Otology, Price et al challenge a previously held view concerning a relationship between hand dominance and nasal airflow laterality. [2][3][4] In this most recent study, no correlation between nasal airflow dominance and handedness was identified. 2 Their results argue against the existence of a dominant nasal passage.…”
mentioning
confidence: 73%
“…My focus was on: (a) existing evidence from lesion, inactivation, imaging and EEG studies, as well as repetitive TMS (rTMS) treatment studies, for hemispheric asymmetries of mood and mood disorders (for citations see Pettigrew & Miller, 1998; see also endnote 16) and (b) a little‐known existing literature on ultradian rhythms of alternating cerebral activation, evidenced centrally by alternating asymmetries in scalp prefrontal EEG, and peripherally by alternating asymmetries of nasal patency (the nasal cycle). Indeed, the latter literature had already proposed the existence of a ~90‐minute IHS in animals and humans (reviewed in Shannahoff‐Khalsa, 1993; see also Price & Eccles, 2016), well predating our search. Appealing to all of these sources, we proposed the sticky interhemispheric switch model of BD (or sticky switch model, for short).…”
Section: Two New Modelsmentioning
confidence: 85%
“…21 Although speculative, from my discussions and observations with mood disorder and healthy subjects, I would expect that in addition to subtle ultradian (hours-long) positive/negative IHS mood rhythms, there will exist a 2-3 day infradian positive/negative IHS mood rhythm (with potentially wide individual variation therein). Just as the hypothalamic-driven ultradian nasal cycle IHS appears to exist in the majority of, but not all, subjects (Kahana-Zweig et al, 2016;Lenz, Teelen, & Eichler, 1985;Price & Eccles, 2016), so too moodrelated ultradian and infradian IHS rhythms may not exist in all subjects. Nonetheless, the hours-long and days-long timeframes accord with descriptions of mood shifts in patients and healthy subjects, and ultradian and infradian positive/negative mood rhythms at their extremities, driven by endogenous oscillators, could provide new insight on mechanisms underlying mixed states, ultra-rapid cycling, and ultradian cycling in BD (Blum et al, 2014;Kramlinger & Post, 1996;MacKinnon & Pies, 2006).…”
Section: Related Researchmentioning
confidence: 99%